Fibre segment interferometry using code-division multiplexed optical signal processing for strain sensing applications - Kissinger, Thomas; Charrett, Thomas O. H.; Tatam, Ralph P. (IOP Publishing, 2013)
A novel optical signal processing scheme for multiplexing fibre segment interferometers is proposed. The continuous-wave, homodyne technique combines code-division multiplexing with single-sideband modulation. It uses only one electro-optic phase modulator to achieve both range separation and quadrature interferometric phase measurement. This scheme is applied to fibre segment interferometry, where a number of long-gauge length interferometric fibre sensors are formed by subtracting pairs of signals from equidistantly placed, weak back reflectors. In this work we give a detailed account of the signal processing involved and, in particular, explore aspects such as electronic bandwidth requirements, noise, crosstalk and linearity, which are important design considerations. A signal bandwidth of ±20 kHz permits the resolution of phase change rates of 2.5 × 104 rad s-1 for each of the four 16.5 m long segments in our setup. We show that dynamic strain resolutions below 0.2 nanostrain Hz-0.5 at 2 m sensor gauge length are achievable, even with an inexpensive diode laser. When used in applications that require only relative strain change measurements, this scheme compares well to more established techniques and can provide high-fidelity yet cost-effective measurements.